High‐Temperature Investigation of TeO2–Na2O–ZnO Glasses. Issue 9 (21st May 2022) - de Clermont-Gallerande, Jonathan; Taniguchi, Daiki; Colas, Maggy; Thomas, Philippe; Hayakawa, Tomokatsu
Abstract : Herein, a ternary system of TeO2 –ZnO–Na2 O (TZN) with competitive roles of covalent Zn–O and ionic Na–O bonds in tellurite glassy network is examined for high‐temperature in situ X‐ray diffraction (XRD) and Raman spectroscopy. TZN glasses are doped with Nd2 O3 and the effects of Nd doping on the crystallization of glasses are also written. In situ high‐temperature XRD permits the assignment of each of the differential scanning calorimetry (DSC) crystallization peaks (the first crystallization peak ( T c1 ) is related to sodium‐based crystalline phases, while the second crystallization peak ( T c2 ) is correlated with tellurium‐/zinc‐based crystalline phases). The study of in situ high‐temperature Raman spectroscopy shows that T c1 shows γ ‐TeO2 crystallized phase‐like peaks while T c2 crystallization has more α ‐TeO2 ‐crystallized phase‐like peaks. Comparison at the same temperature (430 °C) permits a first understanding of the structural changes of the glasses in terms of the evolution first to α‐TeO2, ZnO, ZnTeO3, and Zn2 Te3 O8 crystalline phases compared with Na10 Zn4 O9 phase. The ZnTeO3 and Zn2 Te3 O8 crystallization evolution is also compared between the Nd‐doped and nondoped glasses, which gives more insight into the tellurite glass structures. Abstract : This paper presents an in‐depth study of in situ high temperature X‐ray diffraction and Raman spectroscopy of TeO2 –Na2 O–ZnO ternary glass system both as a function of the concentration and with or without Nd 3+ doping. By these increasingly common but still powerful techniques, the attributions of the glass transition temperature and two crystallization temperatures are evidenced.